1993
DOI: 10.2307/3587400
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Understanding of the Distinct Nature of L2 Writing: The ESL Research and Its Implications

Abstract: Dealing effectively with L2 writers requires a clear understanding of the nature of L2 writing. In an attempt to develop such an understanding, 72 reports of empirical research comparing L1 and L2 writing were examined. The findings of this research indicate a number of salient differences between L1 and L2 writing with regard to both composing processes (and subprocesses: planning, transcribing, and reviewing) and features of written texts (fluency, accuracy, quality, and structure, i.e., discoursal, morphosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
350
0
34

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 533 publications
(396 citation statements)
references
References 20 publications
(28 reference statements)
12
350
0
34
Order By: Relevance
“…Silva mentions that his study demonstrated that writers who were asked to do in L1 and L2 dedicated more concentration to producing fabric in L2 than in L1, and discovered content production in L2 more complex and less flourishing. A great deal of the materials produced in L2 were not used in the students' written text (Silva, 1993). Besides, Silva discovered that writers did less arrangement, at the comprehensive and restricted levels.…”
Section: Similarities Of L1 and L2 Writing Strategiesmentioning
confidence: 99%
“…Silva mentions that his study demonstrated that writers who were asked to do in L1 and L2 dedicated more concentration to producing fabric in L2 than in L1, and discovered content production in L2 more complex and less flourishing. A great deal of the materials produced in L2 were not used in the students' written text (Silva, 1993). Besides, Silva discovered that writers did less arrangement, at the comprehensive and restricted levels.…”
Section: Similarities Of L1 and L2 Writing Strategiesmentioning
confidence: 99%
“…First, teachers in higher education rarely assess the typical errors of L2 speakers (Hyland & Hyland 2010a). Secondly, according to Silva (1993), more errors and less general fluency in L2 writing lead to lower scores. This statement is supported by Celce-Murcia (1991) who argues that surface-level errors in university-level writing can have a negative impact on academic performance.…”
Section: The Productmentioning
confidence: 99%
“…Other scholars (Leki, 1990 andZhang, 1995) also address that there are distinctive differences of linguistic knowledge between L2 and L1 writers. The differences may include linguistic proficiency and intuition about language, learning experiences and classroom expectations, a sense of audience and writer, preferences for ways of organizing texts, writing processes and understanding of text uses as well as the social value of different text types (Silva, 1993).…”
Section: Efl Writing Errormentioning
confidence: 99%